Współzależności w polityce wsparcia sektora rolnego - Kułyk, Piotr (Interrelations in the Agricultural Support Policy, 2009)
This paper presents the consideration of mutual relations in agricultural support policy. There is the sketch for conceptualization of interrelation in the agricultural support policy. The examinations of the agricultural price relations to point out that we need to use different price levels. On the assumption that food products are not perfectly homogeneous we have to use differentiated price levels which take into consideration the externalities with the realization of environmental functions and socio-cultural and also connected with the food-safety. If this process is realized through the mediation of first-hand surcharges, this marks the possibility of the enlargement of the supply and like this the internalization of positive externalities. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 39, T. 1, s. 700-706